Improving the Performance of Oil Based Mud and Water Based Mud in a High Temperature Hole using Nanosilica Nanoparticles - Katende, Allan; Sagala, Farad; Norhafizuddin, Hussein; Ismail, Muhamad S. (Colloids and surfaces A: physicochemical and engineering aspects, 2019)
Oil-based mud (OBM), a non-Newtonian fluid, is known for its superior performance in drilling complex wells as well as combating potential drilling complications. However, the good performance may degrade under certain circumstances especially because of the impact of chemical instability at an elevated temperature. The same phenomenon occurs for water-based mud (WBM) when it is used in drilling under high temperature conditions. To prevent this degradation from occurring, numerous studies on utilizing nanoparticles to formulate smart fluids for drilling operations are being conducted worldwide. Hence, this study aims to evaluate the performance of nanosilica (NS) as a fluid loss reducer and a rheological property improver in both OBM and WBM systems at high temperature conditions. This study focuses on the impacts of different nanosilica concentrations, varying from 0.5 ppb to 1.5 ppb, and different mud weights of 9 ppg and 12 pg as well as different aging temperatures, ranging from ambient temperature to 300 °F, on the rheological performance of OBM and WBM. All the rheological properties are measured at ambient temperature, and additionally tests, including lubricity, electrical stability, and high-pressure high-temperature filtration measurements, are conducted, and rheological models are obtained. The performance of nanosilica is then studied by comparing each of the nanosilica-enhanced mud systems with the corresponding basic mud system, taking the fluid loss and rheological properties as the benchmark parameters. Nanosilica shows a positive impact on OBM and WBM, as the presence of nanosilica in the mud systems can effectively improve almost all their rheological properties.
Keywords: Nanosilica, Oil-Based Mud, Water-Based Mud, High Pressure High Temperature, Degradation, Rheological properties